On the applicability of the hot spot stress method to high strength duplex and carbon steel welded details - Karabulut, B; Rossi, B (Elsevier, 2021)
In this paper, the applicability of the hot spot stress method (HSSM) to the study of fatigue behaviour of welded details made of high-strength stainless or carbon steel is investigated. To that purpose, a broad database of fatigue test results was collated from the literature for transverse stiffeners, butt welds and cope holes which are frequently present in highway girder bridges. For each set of test results, the hot spot stress range was evaluated using finite element (FE) models. The fatigue resistance using the HSSM was then computed and compared to that obtained using the well-known nominal stress method (NSM). It is concluded that the HSSM yields less conservative results than the NSM leading to more economic design of the covered range of high-strength steel welded details.